2019
DOI: 10.1002/nsg.12066
|View full text |Cite
|
Sign up to set email alerts
|

VS30 mapping and site characterization in the seismically active intraplate region of Western India: implications for risk mitigation

Abstract: A B S T R A C TWe carried out shallow subsurface investigations at 600 sites covering all types of geological units in the Northwestern Deccan Volcanic Province of India, using the multichannel analysis of surface waves and suspension PS-logging methods. The results reveal that V S30 values are in the range of 760-1500 m/s for granites and Deccan traps, thus enabling their classification as B-class, as per the National Earthquake Hazard Reduction Program recommendations. The Tertiary, Cretaceous, Jurassic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…; Sairam et al . ). It is used for building codes, earthquake resistant design, shake maps or, like in this work, to define a seismic zonation within an urban area.…”
Section: Seismic Noise Analysis and Site Characterizationmentioning
confidence: 97%
See 2 more Smart Citations
“…; Sairam et al . ). It is used for building codes, earthquake resistant design, shake maps or, like in this work, to define a seismic zonation within an urban area.…”
Section: Seismic Noise Analysis and Site Characterizationmentioning
confidence: 97%
“…Although these techniques are available and have been used since the late 1950s, better instrumentation and computational resources developed in the last four decades have resulted in a dramatic increase in the quantity and quality of array recording (e.g. Flores Estrella and Aguirre Gonzalez 2003;Scherbaum, Hinzen and Ohrnberger 2003;Bonnefoy-Claudet et al 2006;Kanli et al 2006;Mohamed et al 2013;Hollender et al 2018;Vicêncio, Teves-Costa and Sá Caetano 2018;Mahajan and Kumar 2018;Pergalani et al 2020;Sairam et al 2019).…”
Section: S E I S M I C N O I S E a N A L Y S I S A N D S I T E C H A mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the derived Vs. profiles were compared between these two different approaches, which were found to be in good agreement. Sairam et al (2019) conducted the MASW survey for 600 sites in the Northwestern Deccan Volcanic Province of India. Their study suggested that Vs. derived from the MASW method is a good proxy for soil classifications.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these crucial V s30 -based maps would provide the potential variations in earthquake shaking due to local site effects based on subsurface ground conditions, such as degree of stiffness and the thickness of the geological materials. These maps are of vital importance in ground motion modeling and probabilistic seismic hazard assessment [10]. Therefore, V s30 is a primary indicator of both the stiffness of near-surface formations and their site effects, since it provides closed-form expressions relating short-and mid-period amplification factors with depth [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%